Ethics and policy of medical brain drain: A review - Kollar, Eszter; Buyx, Alena (Swiss Medical Weekly, 2013)
Health-worker migration, commonly called "medical brain drain", refers to the mass migration of trained and skilled health professionals (doctors, nurses, midwives) from low-income to high-income countries. This is currently leaving a significant number of poor countries, particularly in sub-Saharan Africa, with critical staff shortages in the healthcare sector. A broad consensus exists that, where medical brain drain exacerbates such shortages, it is unethical, and this review presents the main arguments underpinning this view. Notwithstanding the general agreement, which policies are justifiable on ethical grounds to tackle brain drain and how best to go about implementing them remains controversial. The review offers a discussion of the specific ethical issues that have to be taken into account when deciding which policy measures to prioritise and suggests a strategy of policy implementation to address medical brain drain as a matter of urgency.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Ethics; Health-worker migration; Human resources for health; Medical brain drain; Policy